Performance of Mini-Mental State Examination (MMSE) in long-stay patients with schizophrenia or schizoaffective disorders in a psychiatric institute. (30th July 2016) - Ong, Hui Lin; Subramaniam, Mythily; Abdin, Edimansyah; Wang, Peizhi; Vaingankar, Janhavi Ajit; Lee, Siau Pheng; Shafie, Saleha; Seow, Esmond; Chong, Siow Ann
Abstract: Studies have found that age and education were associated with cognition in older adults. However, little is known how clinical factors (e.g. age of illness onset, length of hospital stay, type of antipsychotic medications, and duration of illness) are associated with cognitive functioning in patients with schizophrenia. This study aimed to examine the influence of socio-demographic and clinical factors on cognitive domains measured using Mini-Mental State Examination (MMSE) among patients with schizophrenia or schizoaffective disorders residing in a psychiatric institute in Singapore. A single-phase interview was conducted at the Institute of Mental Health (IMH) in patients diagnosed with schizophrenia or schizoaffective disorders (n=110). MMSE was administered to all participants. Data on socio-demographic characteristics, smoking, alcohol consumption, and medical history were collected. Age, gender, and level of education were significantly associated with MMSE scores. After adjusting for all socio-demographic correlates, longer length of hospital stay remained significant in predicting lower MMSE scores. Length of hospital stay was independently associated with cognitive functioning. Early interventions for cognition such as physical and mental exercises should be implemented for better prognosis. Highlights: Presence of cognitive impairment was identified in 83.6% of patients. Female patients have a significantly higher MMSE score than male patients. Patients with high education level have a significantly higher MMSE score. Patients with youth-onset schizophrenia have a significantly lower MMSE score. Longer length of hospital stay indicated a significantly lower MMSE score.